(3eSGFd abgjIs - (3cGTa GdZWGA, gGOj Hf YHGS Hf Ydj GHf cGTa GdZWGA, J (B1360(3g` (B1941(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3cJGH GdWgGQI, hgj bSeGf(B: (3WgGQI ef GdMOK hWgGQI ef GdNHK, GdbSe GdChd jMUd HKdGKI CehQ GdhVhA hGdZSd hGdJjees
(3BNQgG (B:s
(3BNQgG(B: (3hefg HYde GdMGd dh cGf GdGYJcGa aj TgQ QeVGf hbO LGeY abO dG jchf Ydjg caGQI hbO Jchf hGMOI HJYOO eKfi hKdGK hQHGY hGh (B... (3GdUGFeI cPdc MGd GdGYJcGa HYO GdRhGd hGddg GdYGdes
(3jHOh CfgG eShOI GdeDda deG ajgG cTJ hTWH hJYOjds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B6: 128s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis